Strategi Bisnis Media Bagi CEO Muda di Era Revolusi Informasi - Agus Srimudin; Selly Ratna Sari; Lukman; Mardiana (Jurnal Ilmu Komunikasi Balayudha, 2023)
The war of the media business were getting faster along with the growth of the mass media industry in the current era of information revolution. Media business competitors are not only from mainstream media (media with legal entitas) but also from individuals because of the rise in online media. However, the social media is also rife, enlivening the virtual world, which in fact has become a competitor for the real world. The era of this revolution has made a number major media outlets out of business because they were hit by the wave of new media. To survive, the media is forced to create, innovate, and collaborate. Many media that already exist in large groups have collapsed, especially independent media. However, the unique thing is that new media are growing. Some Media Business strategies for Young CEOs in the Information Revolution Era include Innovation, Creation, Collaboration, forming a solid team and experts in the field of media, and the use of advertising that werw carried out continuously. This if done sustainably can be a young business strategy to run the mass media business.